2022
DOI: 10.1002/alr.23001
|View full text |Cite
|
Sign up to set email alerts
|

Chitogel following endoscopic sinus surgery promotes a healthy microbiome and reduces postoperative infections

Abstract: Background: Postoperative infections following endoscopic sinus surgery (ESS) impair wound healing and lead to poor outcomes. The aim of this study is to assess the effectiveness of Chitogel to reduce postoperative infections and restore a healthy microbiome following ESS. Methods: In this double-blinded randomized control trial, 25 patients undergoing ESS were prospectively recruited. At the end of surgery, patients were randomized to receive Chitogel to one side of the sinuses (allowing the other side to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…A total of 6 studies reported between 2010 and 2022 satisfied the inclusion criteria for the meta‐analysis among the 546 distinctive reports. 10 , 11 , 12 , 13 , 14 , 15 This meta‐analysis study included 386 subjects after endoscopic sinus surgery of nasal polyps at the beginning of the study; 187 were using chitosan‐based gel dressing, and 199 were control. All studies evaluated the effect of chitosan‐based gel dressing on wound infection, synechia, and granulations after endoscopic sinus surgery of nasal polyps.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 6 studies reported between 2010 and 2022 satisfied the inclusion criteria for the meta‐analysis among the 546 distinctive reports. 10 , 11 , 12 , 13 , 14 , 15 This meta‐analysis study included 386 subjects after endoscopic sinus surgery of nasal polyps at the beginning of the study; 187 were using chitosan‐based gel dressing, and 199 were control. All studies evaluated the effect of chitosan‐based gel dressing on wound infection, synechia, and granulations after endoscopic sinus surgery of nasal polyps.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 6 studies reported between 2010 and 2022 satisfied the inclusion criteria for the meta‐analysis among the 546 distinctive reports 10‐15 . This meta‐analysis study included 386 subjects after endoscopic sinus surgery of nasal polyps at the beginning of the study; 187 were using chitosan‐based gel dressing, and 199 were control.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations